(untitled) (CIPEEX, 2025)
MedAgenda is an innovative software designed to transform the daily routines of healthcare professionals by offering an integrated solution for managing patient data, clinical reports, and appointment scheduling. The primary goal is to centralize and streamline the management of patient information, improving efficiency, reducing errors, and ensuring data security. The platform features intelligent scheduling, secure data storage, and advanced search functions, addressing common challenges such as administrative overload, data loss, and diagnostic errors. MedAgenda enables healthcare professionals to focus more on patient care by reducing time spent on administrative tasks.